Evaluation of the Status of Yasouj in terms of City Development Strategy (CDS) Indicators - Ahmad PoorAhmed; Ali Saberi (تحقیقات کاربردی علوم جغرافیایی)
The city development strategy(CDS) is a novel initiative that is currently being implemented in numerous cities worldwide, including several in Iran. Its primary objectives are to enhance the quality of life, combat poverty, promote sustainable development, and foster effective urban management through a participatory approach. The purpose of this study is to examine and compare the perceptions of residents and municipal administrators regarding various aspects of the urban development plan. This study is characterized as descriptive-analytical. The statistical population comprises managers, employees of urban management, and citizens in Yasouj city. The sample size was estimated to be 384 for citizens and 30 for managers using Cochran's method. One-sample t-test, independent t-test, one-way analysis of variance(ANOVA) and multivariate linear regression were used to analyze sample data. The findings of the study reveal that while municipal administrators are generally content with the current state of these dimensions, residents believe that these elements of the urban development plan are not satisfactory. The descriptive statistics and the t-test demonstrate that the overall mean of the urban development plan dimensions is 1.88 from the people's perspective and 2.98 from the viewpoint of urban administrators. Furthermore, the level of satisfaction with the research's dimensions significantly differs between the two groups. The linear regression analysis indicates that, according to the people's perspective, the dimensions of bankability and the ability to live comfortably hold the highest and lowest significance, with coefficients of 0.413 and 0.167, respectively. However, from the perspective of city managers, the dimensions of livability and good governance are the most and least significant, with coefficients of 0.373 and 0.112, respectively. Ultimately, the findings of this study can assist urban managers in making more informed decisions and delivering services that better align with the needs of the community.